Association between thyroid hormones and comorbid psychotic symptoms in patients with first-episode and drug-naïve major depressive disorder. (February 2023) - Peng, Pu; Wang, Qianjin; Ren, Honghong; Zhou, Yanan; Hao, Yuzhu; Chen, Shubao; Wu, Qiuxia; Li, Manyun; Wang, Yunfei; Yang, Qian; Wang, Xin; Liu, Yueheng; et al.
Highlights: Serum levels of thyroid stimulating hormone (TSH), anti-thyroglobulin (TgAb), and thyroid peroxidases antibody (TPOAb) were higher in first-episode drug-naïve major depressive disorder (FEND MDD) patients with psychotic depression (PD) than those without. The presence of subclinical hypothyroidism increased the risk of PD by 9-fold. TSH, HAMA scores, and HAMD scores were independently associated with PD. The combination of TSH, HAMA scores, and HAMD scores excellently distinguished PD patients from non-PD patients. Abstract: Thyroid dysfunction is common in major depressive disorder (MDD) patients; however, its relationship with psychotic depression (PD) remains unclear. We aimed to assess thyroid hormones in 1718 first episode drug naïve (FEND) MDD patients and to determine their association with PD. The positive subscale of the Positive and Negative Symptom Scale (PANSS-P), Hamilton Anxiety Rating Scale (HAMA), and Hamilton Depression Rating Scale (HAMD) were used to detect clinical symptoms. The serum levels of free triiodothyronine (FT3), free thyroxine (FT4), thyroid stimulating hormone (TSH), anti-thyroglobulin (TgAb), and thyroid peroxidases antibody (TPOAb) were assessed. The logistic regression model was conducted to determine risk factors for PD, and the Area Under the Curve (AUC) was used to test the performance of this model. 171 (10%) patients were identified as having PD. Serum levels of TSH, TgAb, and TPOAb displayed small-to-moderate associations with PANSS-P. HAMA score, HAMD score, and TSH levels were independently associated with PD. The regression model had excellent power to distinguish PD patients from non-PD patients with an AUC value of 0.93. Our study suggests TSH levels and severity of depression and anxiety symptoms were independent risk factors for PD. Regular thyroid function tests may help early detect PD.